„Psalmem cichym, nowym”. Psalmy Dawidowe Tarasa Szewczenki a przyswajanie liryki Psałterza w narodowej literaturze pięknej (w dwusetną rocznicę urodzin Ukraińskiego Wieszcza) - Betko, Iryna (Rusycystyczne Studia Literaturoznawcze, 2015)
The article analyses the Psalms of David by Taras Shevchenko in the context of the psalm-reception’s tradition in Ukrainian literature. Also special attention is devoted to the interpretations of the psalms by Vladimir Monomach, Hryhorij Skovoroda, Marcian Shashkevich, Ivan Franko and others.